Impulse Buying Behavior Generasi Milenial: Valuasi Maslahah Fintech Ovo dan Go-Pay - Tutut Alawiyah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2020)
Abstract: The people's consumption behavior continues to experience a shift in line with the increase in income and technological developments that penetrate the financial sector. The availability of convenience through fintech platforms makes the public, especially the millennial generation, moved to change in all fields to meet needs. In meeting needs, inherent characteristics such as short-term thinking, impulsivity and adaptive technology. These three characteristics of buying behavior make the millennial generation more comfortable with the presence of OVO and Go-Pay. OVO and Go-Pay also offer various promos that encourage impulsive buying to get out of hand. In this case, the millennial generation is entering the planned impulse buying type on the use of OVO and Go-Pay because the frequent consumption of the millennial generation is due to the presence of promos/discounts. According to al-Shāṭibī, benefit can be realized by meeting the needs of ḍarūriyāt, hājiyat, and taḥsīniyāt, from which ḍarūriyāt's needs are ensured, welfare is formed before reaching other needs. Because the fulfillment of ḍarūriyāt can prevent oneself from being damaged, that through ḍarūriyāt one understands how to guard al-kulliyāt al-khamsah. However, the facts are inversely proportional to what they should be.